Marketing of Online Ojek Applications to Understand Customer Perception of Loyalty: Literature Study - Fatra Nur Isnania; Yolanda Masnita; Kurniawati Kurniawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Online motorcycle taxi applications are applications that provide public transportation such as motorbikes, cars, and even online motorcycle taxi applications can order food or simply send goods from one place to another. The purpose of this study is to investigate the impact of performance risk and relationship building on customer loyalty, as measured by trust, in online motorcycle taxi applications. This data was obtained in July 2024, as many as 105 respondents were used for validity and reliability testing and path analysis tests, using the hair method, all samples were taken from online motorcycle taxi application users in JABODETABEK. By using path technique analysis to see the direct and indirect paths as dependent variables to the dependent variable. This study yields several key conclusions, including the following: performance risk on customer loyalty, performance risk on trust, and the relationship between performance risk and customer loyalty through trust have no significant effect. However, the variables of relationship building on trust, relationship building on customer loyalty, and trust on customer loyalty have a significant effect.